Remote Inquiry and Virtual Simulation in a Fourier Transform Course: Effects on Critical Thinking Among Prospective STEM Teachers - Verawati, Ni Nyoman Sri Putu; Rapsanjani, Hafsemi (Faculty of Engineering and Applied Science, 2025)
Critical thinking is a stated goal in STEM teacher education but often underdeveloped in courses that emphasize procedures over reasoning. This study examined whether virtual simulation-assisted remote inquiry improves critical thinking among prospective STEM teachers in a Fourier Transform course. We conducted a randomized pretest–posttest control-group design with two intact classes at one university (experimental n = 20, control n = 20). Both groups received the same content, instructor, timing, and assessments. The intervention embedded prediction, observation, explanation, and decision steps inside an LMS using a PhET Fourier simulation. Critical thinking was measured with an eight-item essay test aligned to analysis, inference, evaluation, and decision making, scored 0–4 per item. All students completed pretest and posttest. The experimental mean rose from 10.90 (SD 2.30) to 26.60 (SD 2.10) with high normalized gain (g = 0.74), while the control mean increased from 11.20 (SD 2.10) to 15.10 (SD 2.40) with low gain (g = 0.19). Gain scores met normality, and an independent-samples t-test showed a significant between-group difference, t(38) = 10.94, p < .001. Category shifts mirrored these results, with the experimental group moving to critical and very critical at posttest. Findings indicate that simulation-supported remote inquiry can meaningfully elevate critical thinking in abstract topics and offers a feasible model for teacher preparation.